The condition for the evolution of extra current peak in the cyclic voltammogram of LixMn2O4 investigated by in situ bending beam method - Chung, Kyung Yoon; Kim, Jong Hee; Yoon, Won-Sub; Kim, Hyung Sun; Cho, Byung Won; Kim, Kwang-Bum (ELSEVIER SCIENCE INC, 2009)
The condition for the occurrence of extra current peak near 3.7 similar to 3.9V in CV and the relationship between the intensity of the extra current peak and the volume of phase transformation from tetragonal to cubic phase was investigated using in situ bending beam method. It was found that the extra current peak evolved when the sample was subject to the 3 V range and its intensity increased as the excursion depth to the 3 V range was increased. The in situ bending beam method data revealed that the extra current peak accompanied the tensile strain variation which is due to the phase transformation of a residual tetragonal phase to a cubic phase. Further, it was found that the amount of the phase transformation increased as the excursion depth to the 3 V range increased, i.e. the volume of the phase transformation was proportional to the intensity of the extra current peak. It seems that the phase transformation from tetragonal phase to cubic phase cannot be completed during the voltage sweep at the 3 V peak. On the contrary, the voltage excursions to 4 V range did not affect the evolution of the extra current peak. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: ELECTROSTATIC SPRAY DEPOSITION; RECHARGEABLE LITHIUM BATTERIES; ELECTRODE MATERIALS; STRUCTURAL FATIGUE; SPINEL ELECTRODES; ION BATTERIES; FILMS; OXIDES